A Systematic Review With Consensus Expert Opinion of Best Reconstructive Techniques After Osseous En Bloc Spinal Column Tumor Resection. (15th October 2016) - Glennie, R. Andrew; Rampersaud, Y. Raja; Boriani, Stefano; Reynolds, Jeremy J.; Williams, Richard; Gokaslan, Ziya L.; Schmidt, Meic H.; Varga, Peter P.; Fisher, Charles G.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Systematic literature review and consensus expert opinion. Objective: To provide recommendations on reconstructive constructs for large tumor resections of the spinal column. Four questions were studied: (1) What are the best reconstructive options for single versus multilevel resections? (2) Should short segment fixation be considered in primary tumor reconstruction? (3) How should reconstructive techniques differ at various regions of the spine? (4) Does planned postoperative radiation change the fusion strategy? Summary of Background Data: Primary spinal tumors requiring en bloc resection are rare. Most studies focus on disease-free survival and local recurrence rates. Few studies focus on reconstructive options and outcomes with respect to fusion rates and need for revision. Methods: A literature search was performed from January 1990 to December 2013. Data were combined and construct survivorship summarized. A survey was administered to international spine tumor surgeons, evaluating reconstructive preferences. Results: The search yielded 381 articles, 12 included in the final analysis. Revision rates for anterior reconstruction were similar for autogenous strut grafts (10%), cages (7.7%), and allograft strut grafts (8.3%). There were two reports of revision from short to long segment constructs and three reports of broken pedicle screws, one requiring revision. Expert survey results revealed that most surgeons preferred cages packed with morcelized allograft and autograft (75%) for anterior reconstruction of single-level vertebrectomies, and strut bone grafting at the cervicothoracic junction (65%) and when more than one vertebrae was resected in the mid-thoracic spine (75%). Surgeons may alter their fusion technique if postoperative radiation is planned. Conclusion: Posterior reconstruction with at least two vertebral levels above and below is recommended. Cages should be used for single-level defects and structural bone graft alone, or in combination with a cage, should be used when spanning a defect greater than two vertebral bodies. Planned postoperative radiation may affect fusion strategy. Level of Evidence: N/A